Real-time intelligent decision support system for bridges structures behavior prediction - Quintela, Hélder (2007)
There is an increasing need of deploying automatic real-time decision support systems for civil engineering structures, making use of prediction models based in Artificial Intelligence techniques (e.g., Artificial Neural Networks) to support the monitoring and prediction activities. Past experiments with Data Mining (DM) techniques and tools opened room for the development of such a real-time Decision Support System. However, it is necessary to test this approach in a real environment, using real-time sensors monitoring. This study presents the development of prediction models for structures behavior and a novel architecture for operating in a real-time system.